Neuropathology of childhood‐onset basal ganglia degeneration caused by mutation of VAC14. Issue 12 (7th November 2017) - Stutterd, Chloe; Diakumis, Peter; Bahlo, Melanie; Fanjul Fernandez, Miriam; Leventer, Richard J.; Delatycki, Martin; Amor, David; Chow, Chung W.; Stephenson, Sarah; Meisler, Miriam H.; Mclean, Catriona; Lockhart, Paul J.
Abstract: Objective: To characterize the clinical features and neuropathology associated with recessive VAC14 mutations. Methods: Whole‐exome sequencing was used to identify the genetic etiology of a rapidly progressive neurological disease presenting in early childhood in two deceased siblings with distinct neuropathological features on post mortem examination. Results: We identified compound heterozygous variants in VAC14 in two deceased siblings with early childhood onset of severe, progressive dystonia, and neurodegeneration. Their clinical phenotype is consistent with the VAC14 –related childhood‐onset, striatonigral degeneration recently described in two unrelated children. Post mortem examination demonstrated prominent vacuolation associated with degenerating neurons in the caudate nucleus, putamen, and globus pallidus, similar to previously reported ex vivo vacuoles seen in the late‐endosome/lysosome of VAC14‐deficient neurons. We identified upregulation of ubiquitinated granules within the cell cytoplasm and lysosomal‐associated membrane protein (LAMP2) around the vacuole edge to suggest a process of vacuolation of lysosomal structures associated with active autophagocytic‐associated neuronal degeneration. Interpretation: Our findings reveal a distinct clinicopathological phenotype associated with recessive VAC14 mutations.